COMMON ERRORS IN DERIVATIONAL WORD FORMATION AMONG NON- NATIVE ENGLISH LITERATURE STUDENTS - Nur Abdullah; Atika Puspasari; Purnama Arafah (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study aims to identify the types of errors and the factors causing derivative word formation errors in fourth-semester students of the English Literature Study Program at Bina Darma University. The scope of the study is limited to analyzing errors in the use of affixes (prefixes and suffixes) that change the word class or meaning of the base word, based on students' academic texts. The research method used a qualitative descriptive design with purposive sampling of 10 students. Data were obtained through a 300 word essay writing test, then analyzed using Surface Strategy Taxonomy (Dulay, Burt, & Krashen, 1982) which classifies errors into four types: omission, addition, misformation, and misordering. The results showed that misformation was the most dominant error (48%), followed by addition (24%), omission (20%), and misordering (8%). Causal factors include first language interference, overgeneralization of morphological rules, limited morphological knowledge, and minimal exposure to academic vocabulary. The main conclusion of this study is the need for explicit and structured teaching of derivational morphology in writing courses, accompanied by contextual exercises to improve the accuracy of students' use of derived word forms.